Dynamic Measurements of Plastic Deformation in a Water-Filled Aluminum Tube in Response to Detonation of a Small Explosives Charge - Harold Sandusky; Paul Chambers; Frank Zerilli; Larry Fabini; William Gottwald (Shock and Vibration)
Experiments have been conducted to benchmark computer code calculations for the dynamic interaction of explosions in water with structures. Aluminum cylinders with a length slightly more than twice their diameter were oriented vertically, sealed on the bottom by a thin plastic sheet, and filled with distilled water. An explosive charge suspended in the center of the tube plastically deformed but did not rupture the wall. Tube wall velocity, displacement, and strain were directly measured. The agreement among the three sets of dynamic data and the agreement of the terminal displacement measurements with the residual deformation were excellent.